The Anatolian Journal of Cardiology 2022
DOI: 10.5152/anatoljcardiol.2022.1440
|View full text |Cite
|
Sign up to set email alerts
|

Transcatheter Tricuspid Valve Replacement for Tricuspid Regurgitation: A Systematic Review and Meta-analysis

Abstract: The Anatolian Journal of Cardiology is an international monthly periodical on cardiology published on independent, unbiased, double-blinded and peerreview principles. The journal's publication language is English however titles of articles, abstracts and Keywords are also published in Turkish on the journal's web site.The Anatolian Journal of Cardiology aims to publish qualified and original clinical, experimental and basic research on cardiology at the international level. The journal's scope also covers edit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(6 citation statements)
references
References 34 publications
1
3
0
Order By: Relevance
“…Our analysis showed that the length of stay in an open TVR was almost double that of TTVR [23.07 vs. 9.8]. A study performed by Buğan et al found that the average length of stay was 10.7 days in patients with TTVR, which is similar to our study [14]. Data shows that during cardiac surgery, around 0.2% to 6% of patients can develop post cardiotomy cardiogenic shock, this is characterized by tissue hypo-perfusion and end-organ damage despite adequate preload [38].…”
Section: Discussionsupporting
confidence: 90%
See 1 more Smart Citation
“…Our analysis showed that the length of stay in an open TVR was almost double that of TTVR [23.07 vs. 9.8]. A study performed by Buğan et al found that the average length of stay was 10.7 days in patients with TTVR, which is similar to our study [14]. Data shows that during cardiac surgery, around 0.2% to 6% of patients can develop post cardiotomy cardiogenic shock, this is characterized by tissue hypo-perfusion and end-organ damage despite adequate preload [38].…”
Section: Discussionsupporting
confidence: 90%
“…However, there has been a recent increase in trans-catheter tricuspid valve interventions for severe symptomatic tricuspid valvular diseases, especially in patients at higher risk with isolated tricuspid valve disease [11,12]. These interventions did show an improvement in functional status and reduction in severity of valvular disease and mortality [13,14]. Although, we have seen significant advances in trans-catheter treatments for mitral and aortic valves, transcatheter interventions for tricuspid valve are still in the developmental phase [15].…”
Section: Introductionmentioning
confidence: 99%
“…20 With emerging technology and expertise, TTVR may become an attractive option for patients with prohibitive surgical risk or ineligibility to TTVr. 21 This review highlights patient selection for TTVR, various types of TTVR devices, technical considerations for the procedure, and procedural planning for orthotopic TTVR (prosthetic valve deployed at the tricuspid annulus).…”
mentioning
confidence: 99%
“…We thank the authors for their interest in our article 1 and for sharing their clinical experience with the patients receiving transcatheter tricuspid valve replacement (TTVR) with LuX-Valve in perioperative physiotherapy and nursing intervention.…”
mentioning
confidence: 99%